Foundry machinery exhibit, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - Nowell, Frank H., 1864-1950 (1909)
Caption on image: F.H. Nowell. Official Photographer. Alaska Yukon Pacific Exposition. X2949. PH Coll 727.388 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number